(untitled) (CAHIERS MAGELLANES-NS, 2024)
Objective: This pilot study strives to investigate the efficacy of diode laser and ozone gel in pocket disinfection as adjuncts to scaling and root planing (SRP) in patients with localized moderate periodontitis. Background: Periodontitis is a common inflammatory disease affecting the tissue that supports the teeth. It is distinguished by periodontal attachment loss and alveolar bone degeneration. Standard non-surgical treatment involves SRP, but adjunctive therapies such as diode laser (photodynamic therapy, PACT) and ozone gel have been explored for enhanced antimicrobial effects. Materials and Methods:A split-mouth, single-blind, randomized controlled experiment was implemented on 15 patients with localized moderate periodontitis. Each patient underwent SRP, followed by diode laser treatment (PACT) on one pocket and ozone gel on the other. Clinical parameters, including bleeding on probing (BOP), probing depth (PD), plaque index (PI), and clinical attachment level (CAL), were measured at baseline and one month post-treatment. Results: Both PACT and ozone groups showed significant reductions in BOP, PD, PI, and CAL after one month (P<0.001). At baseline, no significant differences were observed between the two groups. After one month, significant improvements in BOP were noted in the PACT group compared to the ozone group (P<0.05). Both groups demonstrated similar improvements in PD, PI, and CAL, with no statistically significant differences between them. Conclusion: The study revealed that diode laser and ozone gel serve as effective adjuncts to SRP for minimizing periodontal inflammation and improving clinical metrics in patients with chronic periodontitis. However, diode laser therapy showed superior results in reducing bleeding on probing compared to ozone gel. Clinical Significance: The data imply that implementing diode laser therapy into periodontal treatment procedures may give significant benefits in managing periodontal inflammation, notably in minimizing bleeding during probing. Further studies with larger sample sizes and longer follow-up periods are needed to confirm these findings and establish comprehensive clinical guidelines.